Diversity of frogs and their microhabitats in the riparian area of Mahua and Ulu Kimanis substations, Crocker Range Park, Sabah, Malaysia - Rozita Zaini; Anna Wong; Yong Huaimei (Penerbit UMS, 2012)
This study presented the diversity of frog species living in the riparian area at two substations in Crocker Range Park (CRP): Mahua and Ulu Kimanis substations. The microhabitat information of each species was also recorded. Sampling had been carried out from September 2008 to January 2009 and the specimens were collected along eight transects by using Visual Encounter Survey (VES) and hand-grabbing technique.The process of collecting and recording of data, were carried out according to the standard method. A total of 30 species of frogs had been collected along with their substrates and microhabitat information. The Simpson Diversity Index (Ds) for Mahua Substation was slightly higher than in Ulu Kimanis and the substrate of green leaves was found to be the most preferred microhabitat for frogs.